Odd Harmonious Labeling of Pn ⊵ C4 and Pn ⊵ D2(C4) - Sabrina Shena Sarasvati; Ikhsanul Halikin; Kristiana Wijaya (Indonesian Journal of Combinatorics, 2021)
A graph G with q edges is said to be odd harmonious if there exists an injection f:V(G) → ℤ2q so that the induced function f*:E(G)→ {1,3,...,2q-1} defined by f*(uv)=f(u)+f(v) is a bijection.Here we show that graphs constructed by edge comb product of path Pn and cycle on four vertices C4 or shadow of cycle of order four D2(C4) are odd harmonious.